Figures de l’aventurière dans The Eustace Diamonds, d’Anthony Trollope (1873) : le refoulement d’un retour - Jacqueline Fromonot (Cahiers Victoriens et Edouardiens)
However emphatically Trollope denied the fact himself, it is striking that the characterization of the key character of The Eustace Diamonds, Lizzie Eustace, conjures up Thackeray’s fictional creature, Becky Sharp, the heroine of Vanity Fair, who appeared on the literary scene some twenty-five years before. This study first undertakes to assess the influence of the Thackerayan paradigm on Trollope’s creation. The two novelists indeed portray female adventurers — manipulative, immoral social climbers and materialistic, merciless predators, as is made particularly obvious with Lizzie’s intention to keep her husband’s inheritance, the eponymous jewels.Secondly, the resurgence of a former model in Trollope appears through the aesthetic treatment of the heroine, which relies on semantic fields that already pervade Thackeray’s novel — the animalization of the two deceitful characters and the theatricality of their behaviour. And yet, contrary to Thackeray, Trollope abstains from building a fascinating character for the reader, as evidenced by the scarcer use of images and the narrator’s bluntly calling the adventuress a “liar”, which amounts to depriving her of any potential aura.This strategy of constant disqualification allows for the emergence of a clear-cut ethical position, which seems absent from Vanity Fair. In Trollope, all kinds of narrative and stylistic strategies tend to deflate the adventuress and to stigmatize a conduct unambiguously presented as shameful. Consequently Lizzie Eustace becomes a counter-model used for didactic purposes, namely moral edification. It appears therefore that whereas the Horatian satire prevails in Thackeray, the Trollopian persona’s embittered tone recalls the Juvenalian satire aimed at the fallen world it lives in.